ANALYSIS OF USER BEHAVIOR AND INFORMATION NEEDS IN PUBLIC LIBRARY IN DEPOK - Adinda Paramita; Yunus Winoto; Ute Lies Siti Khadijah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
This Study discusses the Relation Betwwen Information Seeking Behavior And User Information Needs (Correlation Study on Information Seeking Behavior And User Information Needs in Depok Public Library). The purpose of this study was to determine the significance between the initiation, topic selection, exploration, focus formulation, collection, & presentation stages in information-seeking behavior by users and the information needs of users at the Depok City Public Library. The method used is a quantitive method with the Spearman Rank correlation test. In measuring information needs the author uses the theory of Kart, Gurevitch, and Haas. Data collection techniques used this study include observation, literature study, and survey. The research population is the users of the Depok City Public Library for the period April-May 2022. The sample in this study uses an accidental sampling teachnique and totals 101 people. The results of this study show the significance between the initiation, topic selection, exploration, focus formulation, collection, & presentation stages in information-seeking behavior by users and the information needs of users at the Depok City Public Library. Keywords: Information seeking behavior, information needs, library